EFL college students writing anxiety of English language education at Universitas Internasional Batam - Pratiwi, Theodesia Lady (ELT Forum: Journal of English Language Teaching, 2021)
Writing is considered to be the most difficult skill to master for EFL students. This experience was faced by English Language Education (ELE) students at Universitas Internasional Batam (UIB). Based on the observation, the results of their writings were not satisfying. This study assumed that the students might feel anxious when they were writing in English. Therefore, this study aims to examine the types and causes of writing anxiety of ELE students at UIB. This study employed explanatory design of mixed method research. The research instruments were questionnaires adopted from SLWAI and CWAI developed by Cheng (2004). To extend the deeper analysis, this study conducted interviews to the high- and low-level writing anxiety students. This study found that the most dominant levels of writing anxiety is high-anxiety (71.43%). In terms of writing anxiety, this study found that cognitive anxiety is the most dominant type with the mean of 26.37. Next, when studying the cause of writing anxiety, the most dominant cause was linguistic difficulties. This result was in line with the interviews with high-and low- writing anxiety students. Students with both high and low writing anxiety still found that linguistic difficulties affect their writing anxiety. Therefore, the learning process at English Language Education needs to be equipped with sufficient linguistic competences in the first year, such as vocabulary, grammar, and punctuation.